S‐Denitrosylation by the C‐Terminal Swinging Arm of R1 Subunit: A Novel Mechanism to Restore Ribonucleotide Reductase Activity. Issue 8 (19th February 2021) - Sengupta, Rajib; Coppo, Lucia; Sircar, Esha; Mishra, Pradeep; Holmgren, Arne
Abstract: Thioredoxin (Trx) system plays a crucial role as an electron donor for ribonucleotide reductase (RNR), which catalyzes the formation of deoxyribonucleotides for DNA synthesis. Here, we show that the S‐nitrosylation of the R1 subunit inhibits RNR catalysis and that the enzyme activity is restored via denitrosylation mediated by shuttle dithiols (in a CXXC motif) of the R1 C‐terminal tail or by an externally supplied R1 C‐terminal peptide (containing vicinal dithiols), in case of a R1 C‐terminal mutant. The Trx system was found to be necessary for regeneration of the oxidized vicinal dithiols in the C‐terminal tail/peptide. Our results with recombinant RNR highlighted the importance of C‐terminal vicinal dithiols of R1, in regenerating the RNR activity of S‐nitrosylated R1 subunits. This study will contribute towards a better understanding of S‐(de)nitrosylation mediated regulation of RNR activity. Abstract : Our Study demonstrated that S‐nitrosylation of the R1 subunit inhibited (Ribonucleotide Reductase) RNR activity and the shuttle dithiols in the C‐terminal swinging arm/tail were capable of denitrosylating R1‐SNO, along with Thioredoxin system, thereby reversing the inhibitory effect of S‐nitrosylation on RNR activity.